Humoral and cellular immune response induced by rVSVΔG-ZEBOV-GP vaccine among frontline workers during the 2013–2016 West Africa Ebola outbreak in Guinea. Issue 31 (26th June 2020) - Boum, Yap; Juan-Giner, Aitana; Hitchings, Matt; Soumah, Aboubacar; Strecker, Thomas; Sadjo, Mariama; Cuthbertson, Hannah; Hayes, Peter; Tchaton, Marie; Jemmy, Jean-Paul; Clarck, Carolyn; King, Deborah; et al.
Highlights: We found rVSVΔG-ZEBOV-GP to be immunogenic at 28- and 180-days post vaccination. At 28 days post-vaccination, seroresponse rate was higher in the high-risk group. There is a significant pairwise correlation at 28 days post-vaccination between assays. One dose of rVSVΔG-ZEBOV-GP induces a cellular response that increased with time. Abstract: Background: As part of a Phase III trial with the Ebola vaccine rVSVΔG-ZEBOV-GP in Guinea, we invited frontline workers (FLWs) to participate in a sub-study to provide additional information on the immunogenicity of the vaccine. Methods: We conducted an open‐label, non‐randomized, single-arm immunogenicity evaluation of one dose of rVSVΔG-ZEBOV-GP among healthy FLWs in Guinea. FLWs who refused vaccination were offered to participate as a control group. We followed participants for 84 days with a subset followed-up for 180 days. The primary endpoint was immune response, as measured by ELISA for ZEBOV-glycoprotein–specific antibodies (ELISA-GP) at 28 days. We also conducted neutralization, whole virion ELISA and enzyme-linked immunospot (ELISPOT) assay for cellular response. Results: A total of 1172 participants received one dose of vaccine and were followed-up for 84 days, among them 114 participants were followed-up for 180 days. Additionally, 99 participants were included in the control group and followed up for 180 days. Overall, 86.4% (95% CI 84.1–88.4) of vaccinated participants seroresponded at 28 days post-vaccination (ELISA- GP) with 65% of these seroresponding at 14 days post-vaccination. Among those who seroresponded at 28 days, 90.7% (95% CI 82.0–95.4) were still seropositive at 180 days. The proportion of seropositivity in the unvaccinated group was 0.0% (95% CI 0.0–3.8) at 28 days and 5.4% (95% CI 2.1–13.1) at 180 days post-vaccination. We found weak correlation between ELISA-GP and neutralization at baseline but significant pairwise correlation at 28 days post-vaccination. Among samples analysed for cellular response, only 1 (2.2%) exhibited responses towards the Zaire Ebola glycoprotein (Ebola GP ≥ 10) at baseline, 10 (13.5%) at day 28 post-vaccination and 27 (48.2%) at Day 180. Conclusions: We found one dose of rVSVΔG-ZEBOV-GP to be highly immunogenic at 28- and 180-days post vaccination among frontline workers in Guinea. We also found a cellular response that increased with time.